2020
DOI: 10.29333/ejgm/7847
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Magnesium Sulfate on Prevention of Post-dural-Puncture Headache in Elective Cesarean in Kamali Hospital

Abstract: Introduction:One of the most common complications of spinal anesthesia in elective cesarean is a headache, known commonly as post-dural-puncture headache (PDPH). Various methods are mainly recommended such as resting and the use of non-opioid analgesics, caffeine, and codeine, but none of them has been fully effective in its treatment. Hence, this study was conducted to evaluate the effect of magnesium sulfate on the prevention of postdural-puncture headache in the elective cesarean.Method: a total of 68 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, the second study is more similar to the present research. In this regard, Mashak et al revealed that infusion of MgSO 4 during cesarean section under spinal anesthesia lowered the severity of spinal anesthesiainduced headache at all times (from 12 hours after surgery to 3 days after surgery) (40). Although the severity of PDPH was decreased in 2 studies by magnesium administration, there are some differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, the second study is more similar to the present research. In this regard, Mashak et al revealed that infusion of MgSO 4 during cesarean section under spinal anesthesia lowered the severity of spinal anesthesiainduced headache at all times (from 12 hours after surgery to 3 days after surgery) (40). Although the severity of PDPH was decreased in 2 studies by magnesium administration, there are some differences.…”
Section: Discussionmentioning
confidence: 99%